Modification: Home-Stay Approach for Urban Conservation of Historical Building in Thailand - Suebsuk, Naphasinee; Nakagawa, Osamu (Nakhara : Journal of Environmental Design and Planning, 2013)
The conservation and restoration campaign along the Amphawa Canal started in 2001. Many development projects launched by public and private sectors bring in a large number of tourists; on the other hand, the development negatively impacts many traditional sites. One approach of the campaign is to revive traditional water-based tourism by stimulating the use of traditional buildings along the canal and modifying them to be used for commercial and tourist accommodation. purposes. This paper addresses the problems of conservation in the face of tourism. It mainly focuses on how private individuals modify historical structures and the users’ points of view on modifi cation of traditional houses to home-stays in Amphawa. Motivational factors from a user scale to community (village) scale according to sustainable tourism concepts are presented through cultural conservation of traditional building design, cultural activities and traditional celebrations, and the local way of life along the Amphawa Canal.